Public administration and political determination: a review of theoretical and rhetorical notions in "healing the nation - Domingo-Almase, Ananda (2004)
Conceptual studies and even political speeches have theorized and epitomized that the immense task of alleviating poverty rests on an efficient, responsive, and incorruptible public bureaucracy. And at the pilot seat of a well functioning administrative machine, it has been posed that the ingenious steering of political leaders is a major-drive towards the direction of national prosperity and unity. Once more, the immense task of government in social and economic development elicits academic introspection of the integral relationship between politics and public administration. How the new political and administrative leadership will be able to carry out its imperative responsibility is a question that this study seeks to ponder on if only to shed light on the theoretical underpinnings of the President's rhetoric of "healing and nation." - Reproduced.
Keywords: Public administration